An ink composition for stamping
Patent Information
- Application Number
- CN202280045271.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-28
- Filing Date
- 2022-10-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-10-28
AI Technical Summary
这些印花方法需要为每个图案准备网框、雕刻滚筒等,因此不适合多品种少批量生产的印花
Smart Images

Figure BDA0004626998230000141 
Figure BDA0004626998230000151
Abstract
Description
Technical Field
[0001] This invention relates to ink compositions for printing. Background Technology
[0002] Previously, screen printing and roller printing were widely used methods for textile printing on fabrics such as cotton, silk, and polyester. These methods require screen frames and engraving rollers for each pattern, making them unsuitable for multi-variety, low-volume production. Furthermore, the washing away of the paste generates significant amounts of wastewater, increasing the environmental burden. In contrast, inkjet textile printing eliminates the need for screen frames or engraving rollers; patterns or colors can be changed simply by altering digital data. Therefore, it is suitable for multi-variety, low-volume production, and wastewater discharge is significantly reduced, leading to its widespread adoption in recent years.
[0003] Inkjet printing methods have used inkjet inks containing pigments and resins to date. For example, Patent Document 1 discloses a pigment printing ink composition containing resin particles, water and organic solvents, and describes that the glass transition temperature of the resin particles is 5°C or less, the content of the resin particles is 6.5% by mass or more relative to the total amount of the ink composition, and the film elongation is 400% or more and 600% or less, and the film strength is 50 MPa or more.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Publication No. 2020-104362 Summary of the Invention
[0007] One aspect of the present invention relates to a printing ink composition comprising a resin, a pigment, an aqueous medium, and an organic solvent, wherein the resin comprises: a first resin having an elongation of 500% or more and 750% or less and a tensile strength of 25 MPa or more and 40 MPa or less; and a second resin having an elongation of 250% or more and 550% or less and a tensile strength of 55 MPa or more and 90 MPa or less. Detailed Implementation
[0008] The invention described in Patent Document 1 above, by containing the resin particles described above in the printing ink composition, is able to form images with good followability to the stretch of fabric and excellent scratch resistance.
[0009] However, when inkjet printing is used for printing, it is necessary not only to improve the traceability but also to improve the colorfastness to rubbing and to prevent the fabric of the printed object from stiffening, so as to achieve a good feel and texture. In this regard, if only resin particles with the specified film elongation and film strength as described above are used, the printed material with the image formed using the ink composition may not be able to obtain sufficient colorfastness to rubbing and texture.
[0010] The following describes in detail the embodiments of the present invention, but the present invention is not limited to these.
[0011] [Printing Ink Composition]
[0012] An embodiment of the present invention relates to a printing ink composition (hereinafter, sometimes simply referred to as "ink composition") containing a resin, a pigment, an aqueous medium, and an organic solvent. Furthermore, the resin contains: a first resin with an elongation of 500% or more and 750% or less, and a tensile strength of 25 MPa or more and 40 MPa or less; and a second resin with an elongation of 250% or more and 550% or less, and a tensile strength of 55 MPa or more and 90 MPa or less. By using this ink composition, printed materials with excellent dry rubbing fastness and wet rubbing fastness can be obtained, and the fabric to which the printing is applied also has a good texture.
[0013] (resin)
[0014] The resin in this embodiment comprises at least two types of resins. The first resin has an elongation of 500% or more and 750% or less, and a tensile strength of 25 MPa or more and 40 MPa or less. The second resin has an elongation of 250% or more and 550% or less, and a tensile strength of 55 MPa or more and 90 MPa or less.
[0015] It is believed that by combining a first resin with high elongation and low tensile strength and a second resin with low elongation and high tensile strength as described above, the resulting printed material can achieve both rubbing fastness and texture.
[0016] In this embodiment, "elongation" and "tensile strength" refer to the values measured in the measurement methods shown in the embodiments described later.
[0017] The first resin has a more preferred elongation of 600% or more and 700% or less, and a more preferred tensile strength of 35 MPa or more and 40 MPa or less.
[0018] As the first resin, any resin having the elongation and tensile strength described above can be used without particular restrictions, but it is preferable to use a resin supplied in an aqueous emulsion state. Considering the ease of mixing with pigments, solvents, and water to prepare ink, and the possibility of dispersing the resin as uniformly as possible in the ink, the first resin is preferably added to the ink in a resin emulsion state, that is, in a state where the resin is stably dispersed with water as the dispersion medium.
[0019] Examples of water-dispersible resins that can be used in this embodiment include polyurethane resins, styrene-acrylic resins, silicone resins, polyester resins, and acrylic resins. Furthermore, copolymers formed by copolymerizing two or more of the above-mentioned resins, such as copolymers of styrene-acrylic resins and polyester resins or copolymers of styrene-acrylic resins and polyurethane resins, can also be used.
[0020] Furthermore, the aforementioned resin can possess reactive functional groups, and it can also be a polymer containing a crosslinking agent. It is believed that, accordingly, when transferred to fabric, some of the resin undergoes crosslinking and strong bonding with the fabric, increasing its molecular weight or initiating a curing reaction, resulting in superior adhesion.
[0021] Furthermore, if the amount of fixing resin added is increased to improve the adhesion stability of the ink to the fabric, the fabric with the transferred image will become stiff and its texture may deteriorate. Therefore, it is preferable to use a resin with a molecular structure that remains flexible even after curing, such as polyurethane resin.
[0022] There are no specific limitations on the specific polyurethane resins; examples include polyurethane resins obtained by reacting polyols with polyisocyanates. More specifically, polymers obtained by urethane linkage of, for example, polyols such as polypropylene glycol, polyethylene glycol, polytetramethylene glycol, poly(ethylene adipate), poly(diethylene adipate), poly(propylene adipate), poly(tetramethylene adipate), poly(hexamethylene adipate), poly-ε-caprolactone, poly(hexamethylene carbonate), organosilicon polyols, and isocyanates such as toluene diisocyanate, 4,4-diphenylmethane diisocyanate, phenyl diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated 4,4-diphenylmethane diisocyanate, isophorone diisocyanate, tetramethylphenyl diisocyanate, etc., or their block copolymers, random copolymers, graft copolymers, etc., can be used.
[0023] As a styrene-acrylic resin, one or more selected from styrene-(meth)acrylic acid copolymer and styrene-(meth)acrylic acid-(meth)acrylate copolymer can be used in combination. As the aforementioned (meth)acrylate, benzyl (meth)acrylate, cyclohexyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, lauryl (meth)acrylate, ethylhexyl 2-(meth)acrylate, ethylhexyl carbitol ester of 2-(meth)acrylate, phenol EO-modified (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl(meth)acrylate, dicyclopentanyl(meth)acrylate, dicyclopentenyloxyethyl(meth)acrylate, etc.
[0024] As silicone resins, modified silicone oils of the side-chain type, single-terminal type, two-terminal type, and two-terminal type can be used.
[0025] As a polyester resin, dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 2,6-naphthalenedicarboxylic acid, sodium sulfoisophthalate, succinic acid, adipic acid, azelaic acid, sebacic acid, 1,10-sebacic acid, and dimer acids, or polycarboxylic acids of three or more esters such as trimellitic acid and benzopyrene, and diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, neopentanediol, 3-methyl-1,5-pentanediol, diethylene glycol, triethylene glycol, polytetraethylene glycol, 1,4-cyclohexanediol, and ethylene oxide adducts of bisphenol A, or polyols of three or more esters such as trimethylolpropane and pentaerythritol, can be used, bonded by esters. Polymers obtained through linkage, or their block copolymers, random copolymers, graft copolymers, etc.
[0026] The second resin has a more preferred elongation of 250% or more and 300% or less, and a more preferred tensile strength of 60 MPa or more and 90 MPa or less.
[0027] As the second resin, any resin having the elongation and tensile strength described above can be used without particular limitations. Specifically, various resins mentioned as the first resin described above can be used.
[0028] The first and second resins can be of the same type or different types. Using the same type of resin for both improves the compatibility between the resins and results in a uniform coating.
[0029] In the ink composition of this embodiment, the weight ratio of the first resin to the second resin (second resin / first resin) is preferably about 0.6 to 1.7. This is considered to achieve a balance between rubbing fastness and texture, particularly excellent dry rubbing fastness. A more preferred range for the weight ratio is 0.8 or more and 1.2 or less.
[0030] Furthermore, in addition to the first resin and the second resin, the resin in this embodiment may also contain other resins besides the first resin and the second resin, without hindering the effect of the present invention.
[0031] Regarding the content of the resin (the sum of the first resin and the second resin) in the ink composition of this embodiment, from the viewpoint of obtaining high rubbing fastness, it is preferably 6% by mass or more relative to the total ink composition; from the viewpoint of improving texture, it is preferably 9% by mass or less relative to the total ink composition. More preferably, the content is 7% by mass or more and 8% by mass or less.
[0032] (pigment)
[0033] The pigment mixed in the ink composition of this embodiment can be, for example, a dispersible pigment that exists dispersed in water. From the viewpoint of obtaining ink with excellent image density, hue, and color stability, the median particle size (D) of the pigment is... 50 Preferably, the wavelength is 30nm or more and 250nm or less, more preferably 70nm or more and 160nm or less.
[0034] Additionally, in this specification, the volume median particle size (D) 50 The measured value is the median particle size obtained using a laser diffraction / scattering particle size distribution measuring device (LA-950 manufactured by Horiba Manufacturing Co., Ltd.).
[0035] As pigments in this embodiment, conventionally known organic and inorganic pigments can be used. Examples of organic pigments include: azo lakes, insoluble azo pigments, condensed azo pigments, chelated azo pigments, and other azo pigments; phthalocyanine pigments, perylene and perylene pigments, anthraquinone pigments, quinacridone pigments, dioxazine pigments, thioindole pigments, isoindole ketone pigments, quinophthalone pigments, and other polycyclic pigments; basic dye lakes, acidic dye lakes, and other dye lakes; nitro pigments, nitroso pigments, aniline black, and daylight fluorescent pigments. Examples of inorganic pigments include carbon black.
[0036] To give more specific examples of pigments, the pigments used for magenta or red include CI Pigment Red 2, CI Pigment Red 3, CI Pigment Red 5, CI Pigment Red 6, CI Pigment Red 7, CI Pigment Red 15, CI Pigment Red 16, CI Pigment Red 48:1, CI Pigment Red 53:1, CI Pigment Red 57:1, CI Pigment Red 122, CI Pigment Red 123, CI Pigment Red 139, CI Pigment Red 144, CI Pigment Red 149, CI Pigment Red 166, CI Pigment Red 177, CI Pigment Red 178, CI Pigment Red 222, etc.
[0037] Examples of pigments used for orange or yellow include CI Pigment Orange 31, CI Pigment Orange 43, CI Pigment Yellow 12, CI Pigment Yellow 13, CI Pigment Yellow 14, CI Pigment Yellow 15, CI Pigment Yellow 17, CI Pigment Yellow 74, CI Pigment Yellow 93, CI Pigment Yellow 94, CI Pigment Yellow 128, and CI Pigment Yellow 138.
[0038] Pigments used for green or cyan include CI Pigment Blue 15, CI Pigment Blue 15:2, CI Pigment Blue 15:3, CI Pigment Blue 16, CI Pigment Blue 60, CI Pigment Green 7, etc.
[0039] In this embodiment, the pigment content is preferably 1% by mass or more and 12% by mass or less relative to the total weight of the ink composition, more preferably 1% by mass or more and 7% by mass or less. By making the pigment content 1% by mass or more, the image density of the formed record can be increased. Furthermore, by making the pigment content 12% by mass or less, ink with high fluidity can be obtained.
[0040] Furthermore, the ink composition of this embodiment preferably contains anionic pigments. Accordingly, the cationic polymer and anionic pigment contained in the processing liquid used with the ink composition in printing undergo an electroreaction and aggregate on the surface of the object being printed, thus suppressing the penetration of resin contained in the ink into the printed material. In other words, it prevents resin from penetrating into the fiber gaps and causing the fibers to stick together, thereby improving the texture (feel, etc.) of the fabric being printed.
[0041] In this embodiment, the pigment is preferably dispersed in a dispersion containing a pigment dispersion resin and used as a pigment dispersion.
[0042] Examples of pigment dispersion resins that can be used in this embodiment include alkali-soluble resins such as styrene-acrylic acid copolymers, styrene-acrylic acid-alkyl acrylate copolymers, styrene-maleic acid copolymers, styrene-maleic acid-alkyl acrylate copolymers, styrene-methacrylic acid copolymers, styrene-methacrylic acid-alkyl acrylate copolymers, styrene-maleic acid half-ester copolymers, vinylnaphthalene-acrylic acid copolymers, and vinylnaphthalene-maleic acid copolymers. Depending on the requirements, one of these resins may be used alone, or two or more may be used in combination.
[0043] (Aqueous medium)
[0044] The aqueous medium contained in the ink composition of this embodiment is a medium with water as its main component. The aqueous medium can function as a solvent or as a dispersion medium. Specific examples of aqueous media include water or a mixture of water and a polar solvent. Examples of polar solvents contained in the aqueous medium include methanol, ethanol, isopropanol, butanol, and methyl ethyl ketone.
[0045] (Organic solvents)
[0046] The organic solvent contained in the ink composition of this embodiment is not particularly limited, and examples include polyols, glycol ethers, etc.
[0047] In particular, by including a polyol in the ink composition, the viscosity of the ink is appropriately adjusted, which is therefore preferred. The polyol contained in the ink composition is preferably a diol or a triol. Examples of diols include diol compounds, and more specifically, examples include ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, and tetraethylene glycol. Examples of triols include glycerol.
[0048] (Additives and manufacturing methods)
[0049] In addition to the essential components (resin, pigment, aqueous medium, organic solvent) described above, the ink composition of this embodiment may also contain surfactants. Preferred examples of surfactants include acetylenic diol surfactants and organosilicon surfactants.
[0050] The content of the surfactant in the ink composition is generally preferably about 0.01 to 3.0% by mass relative to the total ink composition, and more preferably 0.1 to 1.0% by mass.
[0051] Furthermore, the ink composition of this embodiment may also contain known additives (more specifically, solubility stabilizers, drying inhibitors, antioxidants, viscosity modifiers, pH adjusters, and antifungal agents, etc.) as needed.
[0052] When the ink composition contains a pH adjuster, the pH adjuster is not particularly limited, and examples include sodium hydroxide, triethanolamine, and dimethylethanolamine. By including a pH adjuster in the ink composition, the ink composition can be adjusted to the desired pH.
[0053] The pH adjuster in the ink composition of the present invention is preferably 0.01% by mass or more and 1% by mass or less, more preferably 0.05% by mass or more and 0.2% by mass or less. However, the pH adjuster is not limited to the above range, and can be adjusted appropriately according to the desired pH of the ink composition.
[0054] The ink composition used in this embodiment is manufactured, for example, by mixing resin, pigment, aqueous medium, organic solvent, and any other ingredients (e.g., surfactants) as needed using a mixer. The mixing time is, for example, 1 minute or more and 30 minutes or less. After mixing, the mixture is centrifuged to remove foreign matter and large particles such as debris, and filtered to remove fine particles, thereby obtaining the ink composition of this embodiment.
[0055] The ink composition of this embodiment obtained as described above adjusts the physical properties of the ink to be suitable for inkjet printing, and is therefore particularly suitable for inkjet printing, but can also be used in printing machines other than inkjet printing.
[0056] Example
[0057] The present invention will be further illustrated below with reference to specific examples, but the present invention is not limited to any of the examples.
[0058] [Example 1]
[0059] (Preparation of pigment dispersion)
[0060] A stirrer, nitrogen inlet tube, condenser (stirrer), and dropping funnel were set up in a 1000 mL four-necked flask. Next, 100 g of isopropanol and 300 g of methyl ethyl ketone were added to the flask. The contents of the flask were then heated under reflux at 70°C while being bubbled with nitrogen.
[0061] In addition, 40 g of styrene (ST), 10 g of methacrylic acid (MAA), 10 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), and 0.4 g of azobisisobutyronitrile (AIBN) were mixed to obtain a solution. The resulting solution was then placed in a dropping funnel. The solution in the dropping funnel was then added dropwise over 2 hours to the contents of the aforementioned flask, which was under reflux. After the addition was completed, the contents of the flask were further refluxed for 6 hours.
[0062] Next, 50 ml of methyl ethyl ketone containing 0.2 g of AIBN was added dropwise to the flask over a period of 15 minutes. After the addition was complete, the contents of the flask were further heated under reflux for 5 hours. As a result, a styrene-acrylic resin with a mass-average molecular weight (Mw) of 20,000 and an acid value of 100 mg KOH / g was obtained.
[0063] 15 parts by weight of cyan pigment (LIONOL Blue-FG-7330, manufactured by Toyo Tokiseki Co., Ltd., composition: copper phthalocyanine, color index: pigment blue 15:3), 6 parts by weight of resin, 0.5 parts by weight of 1,2-octanediol, and 78.5 parts by weight of water (ion-exchanged water) were placed in a 0.6 L container of a media disperser (DYNO-MILL, manufactured by Willy A. Bachofen (WAB) Co., Ltd.). In addition, the amount of sodium hydroxide (NaOH) required to neutralize the resin was added to the container. The resulting pigment dispersion contained 14.5% by weight of pigment.
[0064] In the neutralization of the resin described above, an aqueous NaOH solution was added to bring the pH of the container contents to 8. Specifically, 1.1 times the mass of the neutralization equivalent of the aqueous NaOH solution was added to the container. The mass of Na to be added to the container was calculated based on the mass of the resin. Furthermore, the mass of water to be added to the container was calculated based on the combined mass of the water contained in the NaOH solution and the mass of the water generated during the neutralization reaction.
[0065] Next, the medium (zirconia beads with a diameter of 0.5 mm) was filled into the container of the disperser to a volume of 70% of the container's capacity. Then, the contents of the container were kneaded for 240 minutes using the disperser filled with the medium at a temperature of 10°C and a circumferential speed of 8 m / s. As a result, a pigment dispersion containing a large number of pigment particles was obtained. The median particle size (D) of the pigment particles contained in the pigment dispersion is shown in the figure. 50 The median particle size (D) of the pigment particles in the pigment dispersion is 100 nm. 50 The measurement was performed using a dynamic light scattering particle size distribution device (ZetasizerNano manufactured by Sysmex Corporation) as the measuring device, and the measurement was performed on a liquid in which the pigment dispersion was diluted 300 times with ion-exchanged water.
[0066] (The mixture of pigment dispersion with other components)
[0067] Using a mixer (THREE-ONE MOTOR BL-600 manufactured by Shin-To Science & Technology Co., Ltd.), 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4 parts by weight of polyurethane resin "HYDRAN AP-10" (manufactured by DIC Co., Ltd., tensile strength 36 MPa, elongation 520%) as the first resin, 4 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., tensile strength 90 MPa, elongation 270%) as the second resin, 0.5 parts by weight of nonionic surfactant (SURFYNOL 420 (registered trademark) manufactured by Nissin Chemical Industry Co., Ltd., component: diol compound with acetylene group), and 3 parts by weight of deionized water were stirred at a rotation speed of 400 rpm to uniformly mix them. Then, the mixture was filtered through a filter with a pore size of 5 μm to remove foreign matter and large particles. As a result, the ink composition of Example 1 was obtained.
[0068] [Example 2]
[0069] Using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4 parts by weight of polyurethane resin "SUPERFLEX (SF) 460" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 25 MPa and an elongation of 750%) as the first resin, 4 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., with a tensile strength of 90 MPa and an elongation of 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound containing an acetylene group), and 3 parts by weight of ion-exchanged water, the ink of Example 2 was obtained by the same method as in Example 1.
[0070] [Example 3]
[0071] Using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 4 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., with a tensile strength of 90 MPa and an elongation of 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound having an acetylene group), and 3 parts by weight of ion-exchanged water, the ink of Example 3 was obtained by the same method as in Example 1.
[0072] [Example 4]
[0073] Using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 4 parts by weight of polyurethane resin "TAKELAC W-6110" (manufactured by Mitsui Chemicals Co., Ltd., with a tensile strength of 55 MPa and an elongation of 550%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound having an acetylene group), and 3 parts by weight of ion-exchanged water, the ink of Example 4 was obtained by the same method as in Example 1.
[0074] [Example 5]
[0075] Using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 5 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 3 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., with a tensile strength of 90 MPa and an elongation of 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound having an acetylene group), and 3 parts by weight of ion-exchanged water, the ink of Example 5 was obtained by the same method as in Example 1.
[0076] [Example 6]
[0077] Using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 3 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 5 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., with a tensile strength of 90 MPa and an elongation of 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound containing an acetylene group), and 3 parts by weight of ion-exchanged water, the ink of Example 6 was obtained by the same method as in Example 1.
[0078] [Example 7]
[0079] Using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 4 parts by weight of polyurethane resin "TAKELAC W-6020" (manufactured by Mitsui Chemicals Co., Ltd., with a tensile strength of 60 MPa and an elongation of 480%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound having an acetylene group), and 3 parts by weight of ion-exchanged water, the ink of Example 7 was obtained by the same method as in Example 1.
[0080] [Example 8]
[0081] Using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 5.3 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 2.7 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., with a tensile strength of 90 MPa and an elongation of 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound containing an acetylene group), and 3 parts by weight of ion-exchanged water, the ink of Example 8 was obtained by the same method as in Example 1.
[0082] [Example 9]
[0083] Using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 2.9 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 5.1 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., with a tensile strength of 90 MPa and an elongation of 270%) as the second resin, 0.5 parts by weight of nonionic surfactant (SURFYNOL 420 (registered trademark) manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound having an acetylene group), and 3 parts by weight of ion-exchanged water, the ink of Example 9 was obtained by the same method as in Example 1.
[0084] [Example 10]
[0085] Using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 3 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 3 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., with a tensile strength of 90 MPa and an elongation of 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound containing an acetylene group), and 3 parts by weight of ion-exchanged water, the ink of Example 10 was obtained by the same method as in Example 1.
[0086] [Example 11]
[0087] Using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4.5 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 4.5 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., with a tensile strength of 90 MPa and an elongation of 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound containing an acetylene group), and 3 parts by weight of ion-exchanged water, the ink of Example 11 was obtained by the same method as in Example 1.
[0088] [Example 12]
[0089] Using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 2.5 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 2.5 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., with a tensile strength of 90 MPa and an elongation of 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound containing an acetylene group), and 3 parts by weight of ion-exchanged water, the ink of Example 12 was obtained by the same method as in Example 1.
[0090] [Example 13]
[0091] Using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 5 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 5 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., with a tensile strength of 90 MPa and an elongation of 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound containing an acetylene group), and 3 parts by weight of ion-exchanged water, the ink of Example 13 was obtained by the same method as in Example 1.
[0092] [Comparative Example 1]
[0093] The ink of Comparative Example 1 was obtained using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4 parts by weight of polyurethane resin "TAKELAC W-6355" (manufactured by Mitsui Chemicals Co., Ltd., tensile strength 35 MPa, elongation 450%) as the first resin, 4 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., tensile strength 90 MPa, elongation 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., component: diol compound having acetylene group), and 3 parts by weight of ion-exchanged water, except that the method was the same as that of Example 1.
[0094] [Comparative Example 2]
[0095] The ink of Comparative Example 2 was obtained using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4 parts by weight of polyurethane resin "SUPERFLEX 460S" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 30 MPa and an elongation of 790%) as the first resin, 4 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., with a tensile strength of 90 MPa and an elongation of 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound having an acetylene group), and 3 parts by weight of ion-exchanged water, except that the method was the same as that in Example 1.
[0096] [Comparative Example 3]
[0097] The ink of Comparative Example 3 was obtained using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4 parts by weight of polyurethane resin "SUPERFLEX E-4800" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 19 MPa and an elongation of 270%) as the first resin, 4 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., with a tensile strength of 90 MPa and an elongation of 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound having an acetylene group), and 3 parts by weight of ion-exchanged water, except that the method was the same as that in Example 1.
[0098] [Comparative Example 4]
[0099] The ink of Comparative Example 4 was obtained using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4 parts by weight of polyurethane resin "TAKELAC WS-5000" (manufactured by Mitsui Chemicals Co., Ltd., tensile strength 50 MPa, elongation 500%) as the first resin, 4 parts by weight of polyurethane resin "ETERNACOLL UW-1527DF" (manufactured by Ube Industries, Ltd., tensile strength 90 MPa, elongation 270%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., component: diol compound having acetylene group), and 3 parts by weight of ion-exchanged water, except that the method was the same as that in Example 1.
[0100] [Comparative Example 5]
[0101] The ink of Comparative Example 5 was obtained using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 4 parts by weight of polyurethane resin "TAKELAC WPB-341" (manufactured by Mitsui Chemicals Co., Ltd., with a tensile strength of 60 MPa and an elongation of 50%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound having an acetylene group), and 3 parts by weight of ion-exchanged water, except that the method was the same as that in Example 1.
[0102] [Comparative Example 6]
[0103] The ink of Comparative Example 6 was obtained using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 4 parts by weight of polyurethane resin "TAKELAC WS-5984" (manufactured by Mitsui Chemicals Co., Ltd., with a tensile strength of 55 MPa and an elongation of 600%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound having an acetylene group), and 3 parts by weight of ion-exchanged water, except that the method was the same as that in Example 1.
[0104] [Comparative Example 7]
[0105] The ink of Comparative Example 7 was obtained using 20 parts by weight of pigment dispersion, 30 parts by weight of propylene glycol, 4 parts by weight of polyurethane resin "SUPERFLEX 470" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a tensile strength of 40 MPa and an elongation of 640%) as the first resin, 4 parts by weight of polyurethane resin "TAKELAC WS-5000" (manufactured by Mitsui Chemicals Co., Ltd., with a tensile strength of 50 MPa and an elongation of 500%) as the second resin, 0.5 parts by weight of nonionic surfactant ("SURFYNOL (registered trademark) 420" manufactured by Nissin Chemical Industry Co., Ltd., with the component being a diol compound having an acetylene group), and 3 parts by weight of ion-exchanged water, except that the method was the same as that in Example 1.
[0106] The composition of the ink compositions of the above-obtained examples and comparative examples is summarized in Table 1.
[0107]
[0108] (Measurement of tensile strength and elongation)
[0109] The tensile strength and elongation of the resins used in the examples and comparative examples were measured as follows.
[0110] First, the resins were coated onto a PET film to achieve a dried film thickness of 500 μm, and then dried at 25°C and 50% RH for 12 hours. Next, after drying at 150°C for 20 minutes, the resin was peeled off from the sheet to produce the resin film.
[0111] Next, the elongation of the obtained resin film was measured using a tensile testing machine at a measurement temperature of 20°C and a measurement speed of 200 mm / min. The elongation was measured by stretching the resin film and measuring the length of elongation at which the resin film breaks, and the proportion was expressed as an elongation percentage.
[0112] In addition, the tensile strength of the resin is obtained by measuring the tensile strength of the resin at fracture.
[0113] In this evaluation, the tensile testing machine used is the "TENSILON Universal Testing Machine RTC-1210A" manufactured by Orientech Co., Ltd.
[0114] The tensile strength and elongation of the various resins used as resins are summarized in Table 2.
[0115] Table 2
[0116]
[0117] <Evaluation Experiment>
[0118] The following evaluation tests were conducted using the ink compositions obtained in the examples and comparative examples described above.
[0119] (Texture Evaluation)
[0120] An image forming apparatus (an inkjet recording unit equipped with a line head, manufactured by Kyocera Office Information Systems Co., Ltd.) was used as the evaluation machine, and the evaluation was conducted at 25°C and 50% RH. 120g / m² polyester tweed was used. 2 (Manufactured by Toray Industries, Inc.) as the recording medium.
[0121] A solid image of 28cm × 3cm was formed by spraying 35pL of ink (per pixel) from the recording head onto the recording medium. The printed evaluation image was then dried at 160°C for 3 minutes.
[0122] The fabric and the printed image were folded in half, and the height of the fabric when folded in a direction perpendicular to the longitudinal direction was measured / recorded. The texture was evaluated using the following benchmarks as evaluation values.
[0123] Evaluation Criteria:
[0124] ○: Bending height less than 26mm
[0125] Δ: Bending height 26mm~27mm
[0126] ×: Bending height is 28mm or more
[0127] (Evaluation of color fastness to rubbing)
[0128] An image forming apparatus (an inkjet recording device equipped with a line head, manufactured by Kyocera Office Information Systems Co., Ltd.) was used as the evaluation machine, and the evaluation was conducted at 25°C and 50% RH. 120g / m² polyester tweed was used. 2 (Manufactured by Toray Industries, Inc.) as the recording medium.
[0129] A solid image of 28cm × 3cm was formed by spraying 35pL of ink (per pixel) from the recording head onto the recording medium. The printed evaluation image was then dried at 160°C for 3 minutes.
[0130] Then, the printed matter was evaluated by dry and wet tests according to the friction tester type II (mechanical vibration) method as described in JIS L-0849:2013 (Test method for color fastness to rubbing).
[0131] The rubbing cloth used was cotton fabric (Kanakin No. 3), and the rubbing was performed using a rubbing test apparatus (trade name: RT-200, manufactured by Daiei Scientific Instruments Co., Ltd.). After rubbing, the three areas with the deepest color transfer intensity in the color transfer area on the cotton fabric were visually identified, and the color was measured using a colorimeter (trade name: Portable Reflectance Density Meter RD-19 (manufactured by Grinda McBeath)). The degree of color transfer, i.e., the rubbing fastness, was evaluated using the average value of the optical density (cyan). In this test, a dry rubbing fastness rating of C or higher and a wet rubbing fastness rating of E or higher were considered practically applicable.
[0132] Evaluation Criteria:
[0133] A: The optical concentration (cyan) of color transfer in the rubbed cotton fabric is less than 0.15.
[0134] B: The optical concentration (cyan) of color transfer in the rubbed cotton fabric is greater than 0.15 and less than 0.20.
[0135] C: The optical concentration (cyan) of color transfer in the rubbed cotton fabric is greater than 0.20 and less than 0.25.
[0136] D: The optical concentration (cyan) of color transfer in the rubbed cotton fabric is greater than 0.25 and less than 0.30.
[0137] E: The optical concentration (cyan) of color transfer in the rubbed cotton fabric is greater than 0.30 and less than 0.35.
[0138] F: The optical concentration (cyan) of the color transferred in the rubbed cotton fabric is above 0.35.
[0139] The results of the above evaluation tests are summarized in Table 3.
[0140] Table 3
[0141] Example 1 ○ B E Example 2 ○ C E Example 3 ○ A C Example 4 ○ C E Example 5 ○ B E Example 6 Δ A D Example 7 ○ B E Example 8 ○ C E Example 9 Δ C E Example 10 ○ A D Example 11 ○ A D Example 12 ○ B E Example 13 Δ A D Comparative Example 1 Δ C F Comparative Example 2 Δ C F Comparative Example 3 ○ D F Comparative Example 4 × B D Comparative Example 5 ○ D E Comparative Example 6 ○ D E Comparative Example 7 ○ D E
[0142] (Inspection)
[0143] The results in Table 3 confirm that, by using the ink composition of the present invention, printed materials with good texture and excellent rubbing fastness can be obtained. In particular, a comparison of Examples 5 and 6 with Examples 8 and 9 shows that if the ratio of the second resin to the first resin is 0.6 or more, the dry rubbing fastness is even better. Furthermore, it is also known that if the resin ratio is 1.7 or less, the dry rubbing fastness is even better.
[0144] Furthermore, a comparison of Examples 10 to 11 with Examples 12 to 13 shows that, relative to the overall ink composition, if the resin content is 6% by mass or more, the dry rubbing color fastness is superior. It is also known that, relative to the overall ink composition, if the resin content is 9% by mass or less, the texture is superior.
[0145] On the other hand, when using ink compositions of Comparative Examples 1 to 7 in which at least one of the first resin and the second resin contained in the resin does not meet the requirements of the present invention, the quality of at least one of the texture, dry rubbing fastness and wet rubbing fastness fails to meet the qualified level in the evaluation test.
Claims
1. A printing ink composition, characterized in that, It contains resin, pigment, aqueous medium, and organic solvent, among which, The resin comprises: a first resin with an elongation of 500% or more and 750% or less, and a tensile strength of 25 MPa or more and 40 MPa or less; and a second resin with an elongation of 250% or more and 550% or less, and a tensile strength of 60 MPa or more and 90 MPa or less. The resin content, relative to the ink composition as a whole, is 6% by mass or more and 9% by mass or less. The weight ratio of the first resin to the second resin, i.e., the ratio of the second resin to the first resin, is 0.6 to 1.
7.
2. The printing ink composition according to claim 1, characterized in that, The first resin and the second resin are polyurethane resins.
3. The printing ink composition according to claim 1 or 2, characterized in that, Used for inkjet printing.
Citation Information
Patent Citations
Liquid jetting apparatus, inkjet recording method, and pigment printing ink composition
JP2020104362A
Ink for textile printing inkjet
JP2009215506A
ink
JP2020152783A
Print inkjet water-based ink, and method for producing print matter
JP2021038279A